To Tailor Solutions, You Must Understand the Problems: Nursing Facility Resident Changes of Condition. Issue 12 (19th November 2018) - Carnahan, Jennifer L.; Unroe, Kathleen T.
Abstract : This editorial comments on the article byOuslander et al .